2017
DOI: 10.1038/sj.bdj.2017.273
|View full text |Cite
|
Sign up to set email alerts
|

The Hall Technique 10 years on: Questions and answers

Abstract: It is ten years since the first paper on the Hall Technique was published in the British Dental Journal and almost 20 years since the technique first came to notice. Dr Norna Hall a (now retired) general dental practitioner from the north of Scotland had, for many years, been managing carious primary molar teeth by cementing preformed metal crowns over them, with no local anaesthesia, tooth preparation or carious tissue removal. This first report, a retrospective analysis of Dr Hall's treatments, caused contro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
69
0
22

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(94 citation statements)
references
References 22 publications
0
69
0
22
Order By: Relevance
“…More than one decade ago, a different way of fitting SSCs using the Hall Technique (HT) was introduced, in which no part of the carious lesion is removed; instead, the lesion is sealed under a SSC using glass ionomer cement, and no tooth preparation is performed . This is accomplished by arresting the caries activity under the crown, while preserving tooth tissue and pulp vitality . This less invasive method has proved that carious lesions in primary molars can be successfully treated with this technique in the long run.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…More than one decade ago, a different way of fitting SSCs using the Hall Technique (HT) was introduced, in which no part of the carious lesion is removed; instead, the lesion is sealed under a SSC using glass ionomer cement, and no tooth preparation is performed . This is accomplished by arresting the caries activity under the crown, while preserving tooth tissue and pulp vitality . This less invasive method has proved that carious lesions in primary molars can be successfully treated with this technique in the long run.…”
Section: Discussionmentioning
confidence: 99%
“…7,9,11 In addition, the effectiveness of the HT has been proved in different settings (primary or secondary care), by clinicians with diverse clinical expertise (undergraduate, dental therapist, general practitioner, or specialist) and in different countries (Australia, Brazil, Chile, Germany, India, Netherlands, New Zealand, UK, the United States, etc.). 12 A recent Cochrane review 5 analysed the clinical outcomes for primary molars restored with SSCs compared to those restored with other filling materials, concluding that the use of SSCs for treatment of carious primary teeth, or following pulp treatment, may reduce the long-term failure risk compared to fillings. Nevertheless, despite recommendations and clinical evidence, SSCs are not broadly used by general dentists.…”
mentioning
confidence: 99%
“…), including the concept of sealing the entire carious lesion with a stainless‐steel crown in the Hall Technique (Innes et al . ).…”
Section: Reviewmentioning
confidence: 97%
“…This was considered a radical solution to the problem of the cavitated lesion when it was first demonstrated around 16 years ago, as no local anaesthetic is used to numb the tooth, none of the carious tooth tissues are removed and no tooth is cut away to make room for the crown 33. However, there are now a collection of randomised control trials that have shown this management option to be superior in avoiding dental pain and infection, to any other.…”
Section: Repair Options For Managing Active Cavitated Lesions; Sealinmentioning
confidence: 99%